The monitoring of hydrocyclone underflows and mill feed systems using image processing techniques - Petersen, Kurt R. P.(Kurt Ronald Paul) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D.) -- University of Stellenbosch, 1998.